Legal Consideration in Implementing Artificial Intelligence when Dealing with Patients in Healthcare Services - Yuliana Yuliana (SAPIENTIA ET VIRTUS, 2023)
Artificial intelligence (AI) is applied in large activities of daily life. However, besides the positive sides of AI, there are still many legal concerns about implementing AI in medical practice and healthcare services. Ethical consideration needs legal background involvement. This paper aims to describe the legal consideration in implementing Artificial Intelligence (AI) when dealing with patients in healthcare services. This is a narrative literature review. Literature was searched from Science Direct, Google Scholar, and PubMed. The inclusion criteria are research and review. The exclusion criteria are unavailable in full-text journals. The articles were read twice to reduce the possibility of bias. Finally, the selected articles were summarized and narrated in a review. Possible pitfalls in legal concerns when using Artificial Intelligence when dealing with patients include patient privacy, data sharing, rigorous testing procedure, and expensive process. Unification and harmonization of legal regimes have to be applied for legal regulation. Non-discriminative principles are required to ensure legal liability. Legal concerns about implementing Artificial Intelligence (AI) in healthcare services include patient privacy, data sharing, and testing procedure. Legal liability should be ensured by non-discriminative principles.